ANALISIS PERSEPSI PETANI TERHADAP PENGGUNAAN PESTISIDA KIMIA PADA TANAMAN CABAI RAWIT (CAPSICUM FRUTESCENS L.) DI KECAMATAN PRINGGABAYA KABUPATEN LOMBOK TIMUR - Asasandi, I GN Aryawan; Yusuf, M. (Institute of Computer Science (IOCS), 2025)
The objectives of this study are as follows: (1) to find out how farmers' perceptions influence the use of pesticides on cayenne pepper plants. and (2) to find out how farmers' perceptions of chemical pesticides applied to cayenne pepper plants. This study uses a quantitative research method with a descriptive research type. The location of the study was determined by purposive sampling based on data that the highest cayenne pepper production in East Lombok Regency is in Pringgabaya District. The number of samples was 60 people from 15 villages; each village was sampled by 4 respondents. Data analysis was carried out using a simple linear regression technique processed through SPSS (Statistical Package for the Social Sciences) software version 25 and descriptive analysis using a Likert scale score. The results of the study were: (1) Farmers' perceptions have a significant effect on farmers' decisions in using pesticides for the cayenne pepper plants they cultivate. And (2) farmers' perceptions of the use of pesticides in cayenne pepper cultivation are classified as good.